Numerical study of the behaviour of a surface fire propagating through a firebreak built in a Mediterranean shrub layer. (January 2015) - Morvan, Dominique
Abstract: The efficiency of a firebreak, built in a shrubland has been studied numerically using a multiphase physical model. The physical mechanisms governing the propagation of the surface fire and the consequences upon the temperature signal and the radiative heat flux received by a target located at 1 m above the ground level, have been firstly studied before positioning the firebreak. The role played by the flame and the recirculation of hot gases to the ignition of unburned fuel (especially the dry grass) ahead of the fire front have been clearly identified. Four values of the firebreak width L C (ranged between 5 and 20 m) and 3 values of wind velocities (ranged between 1 and 8 m/s) have been tested. The simulations show that above a threshold value of this parameter, even if a small amount of the fuel located on the opposite side of the firebreak was ignited, the released energy was not sufficient to sustain the propagation of the surface fire after crossing the firebreak. Highlights: The efficiency of firebreak built in a Mediterranean shrub layer has been studied. The problem has been solved numerically in using a multiphase approach. The fire is piloted by the recirculation hot gases inside the fuel layer. The study was focused on the effect of the firebreak width.